Sangeetha Pulapaka
0

STEP 1: Recall what is a sequence

https://www.qalaxia.com/viewDiscussion?messageId=5d1f5ee65bbeee0fdf682c41

STEP 2: Recall what is an arithmetic sequence

https://www.qalaxia.com/viewDiscussion?messageId=5d1f5cf45bbeee0fdf682c3d

STEP 3: Recall how to create a regression formula for an arithmetic sequence

https://www.qalaxia.com/viewDiscussion?messageId=5d201bfc5bbeee0fdf682c7b


STEP 4: Write the regression sequence

The regression sequence for arithmetic sequence is

a_{n} = a_{1} + (n-1) d

Here a_{1} is the first term which is 1, d is the common difference which is -1-1 = -2.

So, the explicit formula for the arithmetic sequence is

a_{n} = 1 + (n-1) -2

a_{n} = 1- 2(n-1)